Treatment through empowerment? : exploring the dynamics of ‘responsibility’ in antiretroviral therapy (ART) in two clinics in the Cape Winelands - Myburgh, Hanlie (Stellenbosch : Stellenbosch University, 2013)
Thesis (MA)--Stellenbosch University, 2013.